P 45 Satisfaction with and safety of repetitive neuromuscular magnetic stimulation in children with headache disorders. (May 2022) - Börner, C.; Staisch, J.; Hauser, A.; Lang, M.; Frohnmüller, M.; Hannibal, I.; Huß, K.; Kruse, S.; Klose, B.; Lechner, M.F.; Sollmann, N.; Landgraf, M.N.; et al.
Abstract : Question To assess the safety of and satisfaction with a repetitive neuromuscular magnet stimulation (NMS) intervention targeting to the upper trapezius muscles (UTM) in pediatric patients with headache disorders. Methods Retrospective chart review including 33 patients with migraine, tension-type headache, or post-traumatic headache, who had received at least one test rNMS session targeting to UTM. In patients choosing to undergo rNMS intervention, adherence rate was calculated based on the number of completed rNMS sessions. For patients undergoing the rNMS intervention, safety of and satisfaction with the intervention were assessed by customized questionnaires. Results 33 patients (13.94 ± 2.51 years; 61% females) received at least a test rNMS session to become acquainted with the stimulation setting, resulting in 182 rNMS sessions. In 142 sessions (78%) no adverse events were reported. 43 adverse events were documented for 40 sessions (22%). Related side effects during stimulation included tingling (32.6%), shoulder pain (9.3%), back pain (9.3%), feeling of heaviness (4.7%), trembling (2.3%), and unpleasant tension (2.3%). Related side effects in-between interventions included muscle sore (25.5%), headache (4.7%), and a short-lasting muscle cramp in the upper arm (2.3%). Adverse events categorized unlikely related to the intervention were described in 3 sessions by 2 patients and included shoulder pain (4.7%) and an electrifying feeling radiating to the right hip (2.3%). In these 33 patients, 6 patients (18%) did not continue after the test rNMS session and 4 patients (12%) who started the intervention did not complete the full treatment. 23 patients (70%) completed 28 rNMS interventions with at least 5 of 6 sessions. At follow-up (FU) of 24 interventions, patients completed the customized satisfaction questionnaire. After 13 interventions (54.2%), the treatment was rated as "the therapy helped very well", after 5 interventions (20.8%) as "the therapy helped well", after 1 intervention (4.2%) as "indecisive", after 3 interventions as "the therapy rather did not help", and after 2 interventions as "the therapy did not help". At FU of 25 interventions, patients completed the customized questionnaire regarding repetition of the treatment. After 23 interventions (88.5%), patients would repeat the treatment. At FU of 19 interventions, patients completed the questionnaire regarding recommendation of treatment. After 18 interventions (96.2%), patients would recommend rNMS to other affected patients. Conclusion Stimulation by rNMS was found to be a feasible, safe, and well-accepted treatment option for children and adolescents with headache disorders. Thus, rNMS of the UTM may become a valuable non-invasive, non-pharmacological treatment option for pediatric headache disorders.